Platelet-mediated shedding of NKG2D ligands impairs NK cell immune-surveillance of tumor cells - Stefanie Maurer; Korbinian Nepomuk Kropp; Gerd Klein; Alexander Steinle; Sebastian P. Haen; Juliane S. Walz; Clemens Hinterleitner; Melanie Märklin; Hans-Georg Kopp; Helmut Rainer Salih (OncoImmunology, 2018)
Platelets promote metastasis, among others by coating cancer cells traveling through the blood, which results in protection from NK cell immune-surveillance. The underlying mechanisms, however, remain to be fully elucidated. Here we report that platelet-coating reduces surface expression of NKG2D ligands, in particular MICA and MICB, on tumor cells, which was mirrored by enhanced release of their soluble ectodomains. Similar results were obtained upon exposure of tumor cells to platelet-releasate and can be attributed to the sheddases ADAM10 and ADAM17 that are detectable on the platelet surface and in releasate following activation and at higher levels on platelets of patients with metastasized lung cancer compared with healthy controls. Platelet-mediated NKG2DL-shedding in turn resulted in impaired “induced self” recognition by NK cells as revealed by diminished NKG2D-dependent lysis of tumor cells. Our results indicate that platelet-mediated NKG2DL-shedding may be involved in immune-evasion of (metastasizing) tumor cells from NK cell reactivity.